(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
In the article, Mount Mordecai used a variety of artistic and psychological imaging tools to promote the story of events in the story of "The Stars Burn Forever," has been chosen as a way to provide spiritual proof of reality in artistic description .